MANGO LEAF WEBBER MANAGEMENT USING LEAF- WEB REMOVING DEVICECOUPLED WITH INTEGRATED APPROACHES - M. SURESH, M. SUNIL KUMAR, G. SHIVACHARAN, M. RAGHUVEER, N. R. G. VARMA and Y. PRAVEEN KUMAR (The Journal of Research, PJTSAU, 2026)
Leaf webber (Orthaga spp., commonly O. exvinacea Hampson) is an important defoliator of mango (Mangifera indicaL.), reducing canopy photosynthetic area, weakening shoots, causing extensive defoliation and a characteristic “burnt” appearanceof the canopy, ultimately leading to substantial yield losses. Mechanical removal of webbed shoots and burning of collectedmaterial is a recommended and effective component of integrated pest management (IPM).To develop a sustainable and effectivemanagement strategy, an integrated pest management (IPM) approach was evaluated under field conditions in Adilabad districtof Telangana. The study assessed a combination of mechanical and judicious chemical management methods. The ICAR-CentralInstitute for Subtropical Horticulture (CISH), Lucknow, has developed a simple leaf-web removing device intended to safely andefficiently remove webbed leaves and shoots from mango trees for destruction. The perusal of the data indicated that theimplementation of an IPM module, combining cultural practices like the mechanical removal and destruction of infested webs andshoots followed by targeted insecticidal applications, significantly reduced the leaf webber incidence and increased B:C ratio2.59:1compared to farmer’s practice1.79:1. Mechanical control was found to be highly effective in initial reduction of larval populations(recorded minimal larvae per tree shortly after application).The IPM strategy provided a significant yield increment 27.12 %compared to farmers’ traditional practices. This integrated strategy offers a viable and robust solution for mango growers tomitigate the damage caused by the leaf webber and ensure sustainable mango production.